Mesoscale Eddy Dissipation by a "Zoo" of Submesoscale Processes at a Western Boundary. Issue 11 (21st November 2020) - Evans, Dafydd Gwyn; Frajka‐Williams, Eleanor; Naveira Garabato, Alberto C.; Polzin, Kurt L.; Forryan, Alexander
Abstract: Mesoscale eddies are ubiquitous dynamical features that tend to propagate westward and disappear along ocean western boundaries. Using a multiscale observational study, we assess the extent to which eddies dissipate via a direct cascade of energy at a western boundary. We analyze data from a ship‐based microstructure and velocity survey, and an 18‐month mooring deployment, to document the dissipation of energy in anticyclonic and cyclonic eddies impinging on the topographic slope east of the Bahamas, in the North Atlantic Ocean. These observations reveal high levels of turbulence where the steep and rough topographic slope modified the intensified northward flow associated with, in particular, anticyclonic eddies. Elevated dissipation was observed both near‐bottom and at mid depths (200–800 m). Near‐bottom turbulence occurred in the lee of a protruding escarpment, where elevated Froude numbers suggest hydraulic control. Energy was also radiated in the form of upward‐propagating internal waves. Elevated dissipation at mid depths occurred in regions of strong vertical shear, where the topographic slope modified the vertical structure of the northward eddy flow. Here, low Richardson numbers and a local change in the isopycnal gradient of potential vorticity (PV) suggest that the elevated dissipation was associated with horizontal shear instability. Elevated mid‐depth dissipation was also induced by topographic steering of the flow. This led to large anticyclonic vorticity and negative PV adjacent to the topographic slope, suggesting that centrifugal instability underpinned the local enhancement in dissipation. Our results provide a mechanistic benchmark for the realistic representation of eddy dissipation in ocean models. Key Points: Turbulent dissipation at mid depth linked to sheared flow generated by eddy‐topography interaction Elevated dissipation associated with centrifugal instability where eddy flow was blocked by topography Dissipation in the lee of an escarpment with internal wave generation and possible hydraulic jump